(untitled) (Conference on English Language Teaching, 2023)
The development of technology in educational world requires teachers or educators to be able to use various kinds of learning media in learning and teaching activities. There are many kinds of media which can make the learning more interesting such as Quizizz. This research aims to reveal the potential of this application on English language teaching. This is a systematic review research. The method used in this research is systematic literature review in the purpose of collecting data from Google Scholar and Proquest. The researches found 30 journal articles that discussed similar topics to this current research. Subsequently, it could be classified according to students’ perception in the use of Quizizz, teachers’ perception in the utilization of Quizizz, the use of Quizizz as assessment tool, the use of Quizizz as learning media during pandemic covid-19 and the use of quizizz in general. Thus, this research showed that the Quizizz had positive implementation and good potential in English language teaching activities.